Avaliação da contaminação por parasitos e coliformes em alfaces (lactuca sativa) comercializadas em feiras livres na cidade de Jequié, Bahia. - Rodrigues, Yana Queiroz; Souza, Samilla Gonzaga; Tigre, Dellane; da Silva, Virgínia Maria Góes (Saúde.com, 2021)
In Brazil, more than half of the municipalities do not have basic sanitation plans. This situation affects, in fact, the most economically disadvantaged population, causing the onset of illness by eating raw or poorly washed foods. The present study aimed to analyze the presence of parasites, total and thermotolerant coliforms in lettuces (Lactuca sativa) sold in street markets in Jequié, Bahia. From August to October 2019, the samples were obtained randomly from three street markets, the analyzes were performed by the simple centrifugation method and coliform survey used the Most Probable Number Method. Of the lettuce samples analyzed in street markets, 62.5% showed contamination by hookworm, being the predominant larvae morphology and, the egg was found in only one sample; in addition, it was found that 90.9% of the analyzed samples were positive for thermotolerant coliforms. The presence of hookworms as well as the high count of thermotolerant coliform in samples of lettuce obtained in street markets in the city of Jequié, indicates the need for implementation and adoption of prophylactic measures during the commercialization of vegetable.